A Facile Preparation of Titanium Dioxide-Iron Oxide@Silicon Dioxide Incorporated Reduced Graphene Oxide Nanohybrid for Electrooxidation of Methanol in Alkaline Medium. (20th February 2016) - Yusoff, Norazriena; Kumar, Swadi Vijay; Rameshkumar, Perumal; Pandikumar, Alagarsamy; Shahid, Muhammad Mehmood; Rahman, Marlinda Ab; Huang, Nay Ming
Graphical abstract: Highlights: TiO2 -Fe2 O3 @SiO2 incorporated rGO nanohybrid prepared by hydrothermal method. rGO/TiO2 -Fe2 O3 @SiO2 nanohybrid used for the electrooxidation of methanol. The nanohybrid showed higher electrocatalytic activity toward methanol oxidation. The nanohybrid displayed higher stability with 91.58% retention of the initial jp . Abstract: An iron oxide-silicon dioxide coated titanium dioxide (TiO2 -Fe2 O3 @SiO2 ) incorporated reduced graphene oxide (rGO) nanohybrid was prepared by a simple hydrothermal method using titanium tetraisopropoxide (TTIP) and graphite flakes as the precursors. Tetraethoxysilane (TEOS) was used to form a SiO2 coating on Fe2 O3 nanoparticle surface (Fe2 O3 @SiO2 ). The presence of SiO2 layer would facilitate the formation of Fe2 O3 on the TiO2 surface by an electrostatic attraction that led to the formation of TiO2 -Fe2 O3 @SiO2 . The transmission electron microscopy (TEM) results revealed the successful attachment of Fe2 O3 @SiO2 particles to the TiO2 surface and a uniform distribution of TiO2 -Fe2 O3 @SiO2 composites on the rGO sheet. Furthermore, the rGO/TiO2 -Fe2 O3 @SiO2 nanohybrid modified platinum (Pt) electrode was used for the electrocatalytic oxidation of methanol in alkaline medium. The rGO/TiO2 -Fe2 O3 @SiO2 nanohybrid with weight ratio of 1:3:1 (rGO:TiO2 :Fe2 O3 ) showed a higher electrocatalytic activity toward methanol oxidation with an anodic peak current density of 2.45 mA/cm 2 . Moreover, the nanohybrid displayed a higher stability with 91.58% retention of the initial current density after 5000 s in long term current-time curve. This newly prepared rGO/TiO2 -Fe2 O3 @SiO2 nanohybrid could be a promising anodic catalyst for the direct methanol fuel cells (DMFCs) application.